Impact of HPV Types and Dendritic Cells on Recurrent Respiratory Papillomatosis’ Aggressiveness - Fernandes, Ellen Eduarda [UNESP]; de Almeida Lança, Maria Leticia [UNESP]; de Souza, Yan Aparecido [UNESP]; El-Achkar, Vivian Narana [UNESP]; Costa, Victor [UNESP]; Carlos, Román; Ribeiro-Silva, Alfredo; Sichero, Laura; Villa, Luisa Lina; León, Jorge Esquiche; Kaminagakura, Estela [UNESP] (MDPI, 2025)
Objective: This study assesses the associations between dendritic cells, HPV 6 and 11, and Recurrent Respiratory Papillomatosis (RRP) aggressiveness. Methods: The Derkay score was calculated using information obtained from the medical records. Biopsies from 36 patients with juvenile RRP (JRRP) and 43 adult RRP (ARRP) patients were analyzed under light microscopy, and their clinical data were collected. Immunohistochemical analysis using antibodies against CD83, CD1a, Factor XIIIa, and S100 was performed, and inflammatory cells were quantified. Data obtained were analyzed using the chi-squared test, in addition to the Mann–Whitney and Z tests for two proportions, considering a confidence interval of 95% and p < 0.05 as statistically significant. Results: A higher quantity of S100 was identified in the epithelium (p < 0.001) and in the conjunctive tissue (p = 0.027) among the ARRP cases, while CD83 (p = 0.025) and Factor XIIIa (p = 0.018), both in the epithelium, were identified among the JRRP cases. We observed significant association between a higher quantity of CD83 in the epithelium in the juvenile group with a low Derkay index (p = 0.034) and with HPV 6 (p = 0.039). Conclusions: An increased quantity of dendritic cells is present in individuals diagnosed with RRP, regardless of age, and this may be related to the lower Derkay index, regardless of the HPV type detected.
Keywords: dendritic cells; human papillomavirus virus; inflammatory cells; juvenile laryngeal papillomatosis; laryngeal papillomatosis